Marburg and Sudan viruses elicit divergent interferon responses and cytokine storm signaling in Egyptian rousette bat macrophages - Yordanova, Ivet A.; Arnold, Catherine E.; Corrales, Nicolas; Guito, Jonathan C.; Lander, Angelika; Ang, Lay Teng; Towner, Jonathan S.; Prescott, Joseph B. (Frontiers in Immunology, 2025)
IntroductionEgyptian rousette bats (ERBs) are the only known natural reservoir of Marburg virus (MARV), etiologic agent of a highly-pathogenic zoonotic viral hemorrhagic fever. Evolutionary adaptations in ERBs allow for fine-tuned discrete pro-inflammatory immune responses that control MARV infection, yet permit population-level viral maintenance.MethodsTo look for exclusive co-adapted responses between ERBs and MARV, we compared macrophage (MΦ) responses to MARV and Sudan virus (SUDV), a related filovirus not hosted by ERBs. We queried whether MARV counters normal ERB MΦ responses, illuminating co-adapted host responses not observed upon infection with SUDV, which fails to establish a productive infection and is efficiently immunologically cleared by ERBs.ResultsWe observed stark differences in MΦ transcriptional responses to MARV and SUDV, including differences in type I and III interferon (IFN)-related genes, cytokines, chemokines, cell growth and proliferation genes. We show for the first time that while MARV-infected bat MΦs undergo muted IFN responses and cytokine storm signaling, SUDV induces unperturbed type I and III IFN gene expression, stronger cytokine and chemokine responses resembling typical host responses to a foreign viral pathogen.DiscussionOur findings corroborate growing evidence of unique coevolutionary relationships between bats and the specific viruses they harbor.